Environmental restoration and design for recreation and ecotourism - France, R. L. (CRC Press, 2012)
"A wetland center in London, parks in downtown San Francisco, a wildlife sanctuary in Arcata, and a wetlands park on the outskirts of Las Vegas--what do these urban and suburban locations have in common? They are leading examples of a new restoration design approach that is squarely placed at the interface of nature and culture. This multidisciplinary paradigm bridges the gap between an ecological approach preoccupied with returning damaged landscapes to an imagined original state and a landscape design approach concerned with creating a place for people to reinhabit.Environmental Restoration and Design for Recreation and Ecotourism is the first book to provide a detailed examination of the entire process of restoring damaged or abandoned landscapes to benefit both nature and people, specifically for the purposes of recreation and ecotourism. With a focus on history, planning, methodology, design, and construction, it explores five case studies of successful regenerative landscape design projects and gives readers an inside look at the evolution of design projects. Two of the cases offer a particularly comprehensive review of award-winning projects: the reparation of the degraded Las Vegas Wash into Clark County Wetlands Park and the transformation of the abandoned Barn Elms Reservoirs into the London Wetland Centre. Supported by extensive photographs, tables, maps, sketches, and schematics, these case studies trace how ideas are first conceived and then adopted, transformed, or even abandoned along the way. Each case study also includes a questions-and-answers discussion with designers and managers. Emphasizing the need for interdisciplinary cooperation, the book presents lessons learned from some of the most innovative projects in regenerative landscape design"-- Provided by publisher.
Keywords: Restoration ecology -- Case studies.; Landscape design -- Case studies.; Ecotourism -- Case studies.; Outdoor recreation -- Environmental aspects -- Case studies.; elektronické knihy; electronic books